2023
DOI: 10.4236/ojas.2023.131007
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Antimicrobial Use and Resistance among Village Animal Health Workers and Veterinary Drug Retailers in Cambodia

Abstract: Misuse, overuse, and missed prescription of antimicrobials are the driving factors to antimicrobial resistance (AMR) leading to a globally increasing public health concern. This study was conducted to assess the current knowledge, attitudes, and practices (KAP) of village animal health workers (VAHWs) and veterinary drug retailers (VDRs) on antimicrobial use (AMU) and antimicrobial resistance (AMR). The sample size was calculated following [1]. KAP data were scored and categorized following Bloom's cut-off sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Only two previous studies have investigated education level among veterinary drug retailers in Southeast Asia (SEA), both conducted in Cambodia. The first one showed, similar to the current study, that a majority of respondents had a university education (Heyman, 2020 ), while the other showed that secondary school or high school education was the most common (Chea et al., 2023 ). Hence, the limited number of studies makes it difficult to put the results from the current study into perspective.…”
Section: Discussionsupporting
confidence: 81%
“…Only two previous studies have investigated education level among veterinary drug retailers in Southeast Asia (SEA), both conducted in Cambodia. The first one showed, similar to the current study, that a majority of respondents had a university education (Heyman, 2020 ), while the other showed that secondary school or high school education was the most common (Chea et al., 2023 ). Hence, the limited number of studies makes it difficult to put the results from the current study into perspective.…”
Section: Discussionsupporting
confidence: 81%